Development and investigation of in-vitro sustained release potential of montmorillonite-chitosan microbeads of cefaclor (Journal of Pharmaceutical Negative Results, 2022)
The oral drug administration is most appropriate route for drug delivery to patients. But this route is allied with several drawbacks such as frequency of administration as well as gastric distress. To avoid these problems attempt was made to develop the sustained release system by using nanocomposite clay (MMT), polymer chitosan (CS) and crosslinking agent STPP based microbeads for oral administration of Cefaclor (CF). The formulations were optimized and validated by using Box–Behnken design with 3 different levels of MMT, CS and STPP, wherein the %EE and % drug release at 8 h were considered as dependant responses. The prepared formulation was characterized for FT-IR, DSC and XRD. The optimized formulation was evaluated for various studies like % yield, swelling behavior, particle size, in- vitro drug release and surface morphology studies. The prepared formulation showed physical interaction due to surface adsorption and intercalation of drug with that of MMT. The optimized formulation showed good yield, %EE and swelling behavior due to high amount of MMT, chitosan polymer and STPP crosslinking agent. The size of the microbeads particle was <500 µm and the drug release takes place in slow and sustained manner up to 8 h. Polymeric cross-linking and MMT stalking were observed in FE-SEM study indicated unique. Drug release followed the non-fickian diffusion pattern coupled with matrix release as indicated by Korsemeyer-Peppas (n) value of 0.3228.